Pengaruh Modal Intelektual Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Ririn Yuliawati; Natasia Alinsari (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to analyze and provide empirical evidence whether profitability moderates the relationship between intellectual capital and increasing firm value on the IDX. This study uses secondary data in the form of annual reports of banking companies from 2018-2020. This research method is included in quantitative descriptive research using purposive sampling technique using certain criteria as a determination. The sample in this study were 35 banking companies and the number of observations or observations was 105 data. The data analysis tool used is multiple linear regression and Moderated Regression Analysis (MRA) with the help of Eviews version 10 software. The results show that the intellectual capital variable has an effect on firm value measured using Tobin's Q. There is a moderating variable in profitability as measured by Return On Assets (ROA) is proven to be able to moderate the influence of intellectual capital on firm value. The conclusions in this study is the companies that use optimal intellectual capital can increase the value of the company. Companies that have high profitability are also considered to have high performance in making profits. High profit generated and optimal use of intellectual capital will make the market give more assessments through their share prices.